2005
DOI: 10.1080/10401230591002129
|View full text |Cite
|
Sign up to set email alerts
|

A Description of Next-Step Switching Versus Augmentation Practices for Outpatients with Treatment-Resistant Major Depressive Disorder Enrolled in an Academic Specialty Clinic

Abstract: In this nonrandomized, naturalistic treatment setting, nonresponders to an adequate, prospective antidepressant trial were more likely to have their antidepressant regimen switched, while patients with incomplete response during the first trial were more likely to have their regimen augmented. In addition, patients with incomplete response who had their treatment augmented had better outcome than patients with incomplete response who had their treatment switched.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…However, no supporting data are available regarding the superiority of one strategy over other treatment options. As was seen in surveys with clinicians and treatment choice in the STAR*D trial, augmentation is potentially favoured in partial responders [17][18][19][20][21][22]. This is primarily based on practical considerations, namely that the addition of a second agent allows the initial response to be maintained, whereas a switch might not.…”
Section: Clinical Issues In the Use Of Atypical Antipsychotics In CLImentioning
confidence: 99%
“…However, no supporting data are available regarding the superiority of one strategy over other treatment options. As was seen in surveys with clinicians and treatment choice in the STAR*D trial, augmentation is potentially favoured in partial responders [17][18][19][20][21][22]. This is primarily based on practical considerations, namely that the addition of a second agent allows the initial response to be maintained, whereas a switch might not.…”
Section: Clinical Issues In the Use Of Atypical Antipsychotics In CLImentioning
confidence: 99%
“…There is a strong body of evidence for a role of the DA system in depression (for review, see Papakostas et al, 2005;Willner, 1997). Thus, reduced levels of DA and its metabolites (Roy, 1988;Roy et al, 1992), increased DA D2/D3-receptor binding (Klimek et al, 2002) and reduced DA transporter (DAT) binding (Neumeister et al, 2001) were observed in depressed and/or suicidal patients.…”
Section: Introductionmentioning
confidence: 95%
“…However, the existence of residual symptoms or lack of remission after 6-12 weeks of treatment with first-line antidepressants could justify second-line options, such as augmentation or combination therapy [22]. The STAR*D findings suggest that remission rates decrease considerably after two failed trials, supporting the recommendation that two failed trials defines treatment resistance.…”
Section: When Is the Best Time To Start Augmentation Or Combination Tmentioning
confidence: 88%
“…However, the conventional concept for adequate antidepressant treatment is 'wait and see' at least for 6-12 weeks before moving on to the next treatment strategy. Furthermore, there are no definite data or consensus about the most appropriate time for commencing the augmentation agent to current antidepressant yet [22].…”
Section: After 6 Weeks Of Treatment Ms C Was Prescribedmentioning
confidence: 99%